The uraemic hypertensive patient: a therapeutic challenge—right you are (if you think so). (18th November 2020) - Cice, Gennaro; Monzo, Luca; Calo, Leonardo
Abstract: High blood pressure (BP) is a leading cause of chronic kidney disease (CKD) and at the same time represents its most frequent complication. High BP is an independent risk factor for advanced CKD; on the other hand, at least 40% of patients with normal glomerular filtration rate (GFR) and virtually all patients with GFR <30 mL/min are hypertensive. CKD and microalbuminuria are powerful risk factors for cardiovascular morbidity and mortality. Consequently, in uraemic hypertension, it is of utmost importance to carefully manage both high BP and microalbuminuria, in order to slow down the progression of kidney damage and to reduce the incidence of cardiovascular events. The first purpose of the medical treatment in hypertensive patients is to normalize BP, regardless of the drug used. Nevertheless, some drugs have an 'additional' nephroprotective effect at the same BP target achieved. In this regard, first-line drugs are definitely renin–angiotensin–aldosterone inhibitors, mainly for their proved efficacy in reducing hypertension-related kidney damage and proteinuria. Anyway, a combined approach (two or more drugs) is usually needed to achieve the optimal BP target and reduce the worsening of CKD.